Effectiveness of 3D Animation Using Google Sketchup and Lumion as Tourist Attraction Information Media - Amali, Lanto Ningrayati; Sulistio, Rian; Zakaria, Alfian; Dwinanto, Arif (Universitas Negeri Gorontalo, 2023)
3D animation is easy to describe for presenting visual information attractively and realistically, making it an ideal choice for attraction promotion but more difficult to work with. This study aimed to develop 3D animated videos and test their effectiveness as an information medium for promoting tourist attractions. The research method used was the Multimedia Development Life Cycle (MDLC), which consists of six stages: concept, design, material collection, assembly, testing, and distribution. Designing and creating 3D objects using Google SketchUp, rendering them in animation using Lumion, and editing animated videos using Adobe Premiere Pro CC. The results of the feasibility test by media experts show that 95% of the categories are feasible regarding animation quality and appearance. The feasibility test of 35 people as respondents from the community showed that, in terms of aspects of the display, quality, speed, brightness, time duration, and selection of viewing angles, 90% were found to be in very appropriate categories. These results indicate that 3D animated videos developed using Sketchup and Lumion are worthy of use as information media to promote tourist attractions.